2017
DOI: 10.1039/c6bm00898d
|View full text |Cite
|
Sign up to set email alerts
|

Targeting peptide functionalized liposomes towards aminopeptidase N for precise tumor diagnosis and therapy

Abstract: Aminopeptidase N (APN/CD13) is closely related to the growth of cancers and is suggested as a suitable target for anti-cancer therapy. Based on the "one-bead-one-compound" (OBOC) approach on a microarray device, we screened out a novel affinity peptide LN (YEVGHRC). It was determined that LN could specifically recognize and bind to APN. Moreover, LN-functionalized liposomes (LN-LS) could achieve efficient nano-encapsulated drug delivery under APN-overexpressing tumor conditions in vitro and in vivo. We expect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…As a result, Slp-coated liposomes have received increasing attention in the past decade. Liposomes are nanovesicles composed of phospholipid bilayers that have various beneficial characteristics, such as good cell affinity, 7,8 targeting properties, [9][10][11] and sustained drug-release behavior. 12 Due to their favorable ability to encapsulate both hydrophobic and hydrophilic drugs, liposomes are widely used as carriers for bioactive drugs, including antineoplastic drugs, 13,14 antimicrobial drugs, 15 antiparasitic drugs, 16 hormonal drugs, 17 proteins, 18,19 and nucleic acid drugs 20,21 such as DNA [22][23][24] and siRNA.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, Slp-coated liposomes have received increasing attention in the past decade. Liposomes are nanovesicles composed of phospholipid bilayers that have various beneficial characteristics, such as good cell affinity, 7,8 targeting properties, [9][10][11] and sustained drug-release behavior. 12 Due to their favorable ability to encapsulate both hydrophobic and hydrophilic drugs, liposomes are widely used as carriers for bioactive drugs, including antineoplastic drugs, 13,14 antimicrobial drugs, 15 antiparasitic drugs, 16 hormonal drugs, 17 proteins, 18,19 and nucleic acid drugs 20,21 such as DNA [22][23][24] and siRNA.…”
Section: Introductionmentioning
confidence: 99%
“…This adds to the retention of natural homeostasis in a biological environment and reduction in the entry of water into the LNPs to avoid premature degradation [ 84 ]. This was validated in a study where LNPs were shown to specifically target tumor sites, including the glioblastoma regions [ 86 , 87 ]. A comparable xenobiotic metabolism was noted in LNPs and food-based lipids that were internally degraded into nontoxic residues.…”
Section: Lnps and The Blood–brain Barriermentioning
confidence: 94%
“…Structural modifications or the addition of targeting sequences to the molecule may improve its imaging properties. Conversely, Jia et al strengthened the APN/CD13 tumour-homing ability of YEVGHRC peptide-functionalised liposomes [ 75 ]. They reported that such liposomes could serve as useful tools to carry nano-encapsulated drugs to APN/CD13 expressing tumours under in vitro and in vivo conditions.…”
Section: Overview Of Preclinical Studies With Radiolabelled Ngr-based...mentioning
confidence: 99%
“…Taking into account that the NGR sequence is prone to the deamidation of the Asn side chain, the establishment of less vulnerable APN/CD13 specific peptides is of pivotal importance in angiogenesis imaging [74]. Initial research findings are already available on the diagnostic performance of novel linear sequences directed towards angiogenesis associated biomarkers [40,75]. In a former proof-of-concept study by Dénes et al, the in vivo behaviour of [ 68 Ga]Ga-labelled c(NGR) peptide and linear LN peptide YEVGHRC (tyrosyl-glutamyl-valyl-glycyl-histidyl-arginyl-cysteine)-based radiotracers was studied at the preclinical level (seen in Figure 2) [40].…”
Section: Cendr Sequence-containing Ngr-based Probementioning
confidence: 99%